Enhancing Early Childhood English Vocabulary through YouTube Media: A Case Study at Jitjongkrak School, Krabi, Thailand - Tazkiyatunnupus, Siti Ajeng; Gunawan, Yudhie Indra; Suhendar, Asep (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
English language skills are very important to face future challenges. In situations like this, using video media as a teaching method can be an interesting innovation for teaching children to recognize English vocabulary. This research aims to explore the role of YouTube media in creating a more interactive learning experience and teachers also benefit from YouTube media because YouTube can help teachers explain vocabulary lessons in class, especially in jitjongrak schools, and to increase students' understanding and motivation. This research uses qualitative methods. Researchers will look at the activities of teachers at this school in introducing English vocabulary using animated video media on the YouTube application in learning and describing the problem under study in the real situation by making observations, with the data analysis used, namely descriptive data analysis. The results of the study stated that the English vocabulary ability score of respondents, namely children aged 4-6 years at Jitjongkrak Krabi School, Thailand, who learned English using YouTube media, had an average of 88%, categorized as very good. The existence of YouTube proves that this media can be used as a medium to introduce English vocabulary to children, as evidenced by the average score of YouTube utilization of 62, categorized as good.